2011
DOI: 10.1021/bm200141x
|View full text |Cite
|
Sign up to set email alerts
|

Stress Transfer in Cellulose Nanowhisker Composites—Influence of Whisker Aspect Ratio and Surface Charge

Abstract: The mechanically induced molecular deformation of cellulose nanowhiskers embedded in subpercolation concentration in an epoxy resin matrix was monitored through Raman spectroscopy. Cellulose nanowhiskers isolated by sulfuric acid hydrolysis from tunicates and by sulfuric acid hydrolysis and hydrochloric acid hydrolysis from cotton were used to study how the aspect ratio (ca. 76 for tunicate and 19 for cotton) and surface charges (38 and 85 mmol SO(4)(-)/kg for sulfuric acid hydrolysis of cotton and tunicate, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 35 publications
8
89
0
2
Order By: Relevance
“…75 Using shorter particles as stabilizing agents produced more individualized droplets where as long CNCs bridged droplets creating network-like emulsions. Aspect ratio not only affects interfacial behaviour but impacts, rheological properties, 73 reinforcing capability, 76 and packing of CNCs. 118 Particles with higher aspect ratios, form gels and percolated networks at significantly lower concentrations than shorter particles, potentially reducing the amount of material required for specific applications.…”
Section: "µM"mentioning
confidence: 99%
See 1 more Smart Citation
“…75 Using shorter particles as stabilizing agents produced more individualized droplets where as long CNCs bridged droplets creating network-like emulsions. Aspect ratio not only affects interfacial behaviour but impacts, rheological properties, 73 reinforcing capability, 76 and packing of CNCs. 118 Particles with higher aspect ratios, form gels and percolated networks at significantly lower concentrations than shorter particles, potentially reducing the amount of material required for specific applications.…”
Section: "µM"mentioning
confidence: 99%
“…These studies emphasize that thorough understanding of CNC properties prior to use is critical as differences in particle dimension and charge density can greatly affect the rheological, 73 colloidal, 74 interfacial, 75 and reinforcing properties. 76 Along with the hydrolysis conditions, post extraction treatments such as sonication or purification can further impact CNC properties and behaviour. Beck et al showed that the pitch of chiral nematic phases could be controlled by varying the amount of sonication applied to CNC dispersions.…”
mentioning
confidence: 99%
“…It was suggested that this was due to the higher aspect ratio of the tunicate nanowisker nanocomposite and the absence of charge on the tunicate related to the cotton nanowiskers. 75 When a polymethylmethacrylate nanocomposites with cellulose nanocrystal was prepared by the solution casting method a composite sheets formed from this material retained its transparency. By the thermogravimetric analysis showed to be thermal stable with a significant enhancement of its storage modulus compared with pure one.…”
mentioning
confidence: 99%
“…The procedure has been slightly modified from that described by Rusli et al (2011). NCC was obtained by partial hydrolysis of MCC with 2.4 M HCl solution in a 3 L 3-neck round bottom flask (RBF, equipped with a mixer, reflux condenser, and a glass needle adapter connected to a N 2(g) source) and heating/refluxing in an oil bath at *100°C for 2 h under a steady stream of N 2(g) .…”
Section: Ncc Preparationmentioning
confidence: 99%